Pemaafan pada Perempuan Korban Perkosaan - Dayo, Thasa Dwina Putri; Sari, Kartika; Faradina, Syarifah; Sari, Novita (Jurnal Psikologi TALENTA, 2024)
The purpose of this research is to find out how the forgiveness process in women victims of rape in Banda Aceh. This research uses a qualitative case study method and uses purposive sampling to select participants in this study, namely 3 female victims of rape, and uses in-depth interview techniques for data collection. The results of this study found a different forgiveness process between the three participants. Among them, two of the three participants were still in the uncovering phase where they still felt feelings of anger and resentment towards the perpetrator, even wanting to take revenge. Meanwhile, the other participant's forgiveness process is already in the decision phase, where feelings of anger and resentment towards the perpetrator have decreased and will consider forgiving to the perpetrator. The factors that affected the forgiveness of the three participants were social cognitive, offense characteristics, interpersonal relationship quality, and rumination about transgression.